1990
DOI: 10.1017/s002193200001840x
|View full text |Cite
|
Sign up to set email alerts
|

Endogamy among the Dogon of Boni, Mali

Abstract: This paper examines factors influencing endogamy in a Dogon population in Mali. Situated in Boni district, this population of about 5000 individuals is distributed over fifteen villages located on four independent massifs. This population is strongly endogamous (only 4% of all marriages are contracted with neighbouring ethnic groups), and each massif shows high endogamy. The roles of lineage, residence in the same village, and geographical distance in mating choice are examined. These different factors are suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 2 publications
2
3
0
Order By: Relevance
“…Our results support both a hypothesis of multiple independent origins of populations characterized by their mode of subsistence (the western and central Sahelian pastoralists are different from the eastern ones as inferred by genetic distances and MDS analyses; shown in Figures and ) and a hypothesis of limited gene flow between populations with different subsistence strategies (haplotype sharing between populations is very limited; shown in Figures and ). The limited gene flow observed in our data corroborates the results of ethnographic studies which showed high levels of endogamy in rural Sahelian communities (Cazes, ; Hampshire & Smith, ; Spedini et al, ) and therefore infer that such behavior has been the norm for centuries.…”
Section: Discussionsupporting
confidence: 91%
“…Our results support both a hypothesis of multiple independent origins of populations characterized by their mode of subsistence (the western and central Sahelian pastoralists are different from the eastern ones as inferred by genetic distances and MDS analyses; shown in Figures and ) and a hypothesis of limited gene flow between populations with different subsistence strategies (haplotype sharing between populations is very limited; shown in Figures and ). The limited gene flow observed in our data corroborates the results of ethnographic studies which showed high levels of endogamy in rural Sahelian communities (Cazes, ; Hampshire & Smith, ; Spedini et al, ) and therefore infer that such behavior has been the norm for centuries.…”
Section: Discussionsupporting
confidence: 91%
“…This support of Assumption 2 is in line with Becker (1981), who argues that individuals prefer marriage to a partner who is similar to themselves, and with empirical evidence as the large majority of marriages in rural areas of Sub-Saharan Africa are homogamous (Cazes 1990;Nave 2000). …”
supporting
confidence: 85%
“…Cazes 1990;Nave 2000), even if their families are from different locations. While it is understood that spreading out family ties geographically acts as a coping mechanism against location-specific shocks (Rosenzweig and Stark 1989), the present paper adds a purely economic motivation for intra-ethnicity marriage in developing economies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first long-term demographic and genealogical dataset used in this study comes from a Dogon population in Mali. These data were collected by Marie-Helene Cazes (2016) and obtained via the Kinsources archive: https://www.kinsources.net/kidarep/dataset-186-dogon-boni.xhtml. This population is composed of isolated groups of Dogon, living in the semi-arid climate of the southern Sahel in Mali, around the district of Boni.…”
Section: Data Sources and Ethnographic Overview 211 Dogon From Malimentioning
confidence: 99%